Penerapan Kitab Ta'lim Muta'allim Sebagai Hidden Curriculum Dalam Pembentukan Nilai Religiusitas Di Pondok MA Al-Imaroh - Husna Afifah; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out the application of the Ta'lim Muta'allim book can be a hidden curriculum in learning at Madrasah Aliyah Al-Imaroh, so as to form the religious value of students, this application is expected to make students have good characteristics, can be useful for themselves and others. The method used in this research is a case study method using online interviews. The results of this study are (1) Application of Learning Kitab Ta'lim Muta'allim (2) Application of Hidden Curriculum Learning Kitab Ta'lim Muta'allim (3) Application of Religious Values After Learning Kitab Ta'lim Muta'alim. The implications expected by the application of learning the Ta'lim Muta'allim book, students can apply manners well.